2019
DOI: 10.1080/20009666.2019.1565884
|View full text |Cite
|
Sign up to set email alerts
|

Immune thrombocytopenic purpura

Abstract: Immune thrombocytopenic purpura (ITP) is a bleeding disorder characterized by isolated thrombocytopenia (platelet count <150,000 u/L), which is not associated with a systemic illness. ITP is reported in approximately 2 per 100,000 adults. The mean age of diagnosis is 50 years. ITP is more common in females of childbearing age and in pregnancy. In adults, the course is more chronic although spontaneous remission can also occur within months of initial diagnosis. A thorough and timely workup of thrombocytopenia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…Interestingly, Gialluisi et al identified platelet distribution width (PDW) as a new potential biomarker of depression and psychopathology [ 2 ], for the first time describing the relationship between thrombocytopenia and emotions. ITP is generally regarded as a primary autoimmune condition [ 3 ], yet in some cases, it is observed after other diseases, such as infections [ 4 , 5 ], chronic lymphocytic leukemia and many other autoimmune conditions [ 5 ]. Studies have found that platelet glycoprotein (GP)IIb/IIIa and GPIb/IX are the two most frequently targeted autoantigens and are associated with Fc-FcγR interactions and Fc-independent platelet activation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Gialluisi et al identified platelet distribution width (PDW) as a new potential biomarker of depression and psychopathology [ 2 ], for the first time describing the relationship between thrombocytopenia and emotions. ITP is generally regarded as a primary autoimmune condition [ 3 ], yet in some cases, it is observed after other diseases, such as infections [ 4 , 5 ], chronic lymphocytic leukemia and many other autoimmune conditions [ 5 ]. Studies have found that platelet glycoprotein (GP)IIb/IIIa and GPIb/IX are the two most frequently targeted autoantigens and are associated with Fc-FcγR interactions and Fc-independent platelet activation.…”
Section: Introductionmentioning
confidence: 99%
“…1 Thrombocytopenia typically results in mucosal bleeding consequent to primary hemostasis defect. 1,4 As so, clinical presentation includes epistaxis, gingival bleeding or abnormal uterine bleeding; other common signs are petechiae and ecchymosis. Life-threatening bleeding is infrequent and is restricted to patients with extremely low platelet levels, presenting as hematuria, gastrointestinal bleeding and, rarely, intracranial hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Immune thrombocytopenic purpura is an autoimmune disorder characterized by low platelet count and skin-mucosal bleeding [ 13 ].There are a variety of viruses implicated in the etiopathogenesis of ITP, especially in children, and include human immunodeficiency virus-1, hepatitis C, varicella-zoster, rubella, influenza, and Epstein-Barr virus [ 14 ]. The exact role of viruses in the pathogenesis of this disorder remains ambiguous although ITP typically shadows a viral illness in children.…”
Section: Discussionmentioning
confidence: 99%